Effects of whole-body vibration exercise on bone mineral content and density in thermally injured children. Issue 3 (May 2016) - Edionwe, Joel; Hess, Cameron; Fernandez-Rio, Javier; Herndon, David N.; Andersen, Clark R.; Klein, Gordon L.; Suman, Oscar E.; Amonette, William E.
Highlights: Exercise alone improves muscle mass and muscle strength. Exercise alone does not prevent bone loss in burned children. Combining whole-body vibration with exercise does not further improve strength. Combining whole-body vibration with exercise does not further improve muscle mass. Combining whole-body vibration with exercise may help prevent regional bone loss. Abstract: Background: Loss of bone mass, muscle mass, and strength leads to significant disability in severely burned children. We assessed the effects of exercise combined with whole-body vibration (WBV) on bone mass, lean mass (LM), and muscle strength in children recovering from burns. Methods: Nineteen burned children (≥30% total body surface area [TBSA] burns) were randomly assigned to a 6-week exercise regimen either alone (EX; n  = 10) or in combination with a 6-week WBV training regimen (EX + WBV; n  = 9). WBV was performed concurrent to the exercise regimen for 5 days/week on a vibrating platform. Dual-energy X-ray absorptiometry quantified bone mineral content (BMC), bone mineral density (BMD), and LM; knee extension strength was assessed using isokinetic dynamometry before and after training. Alpha was set at p  < 0.05. Results: Both groups were similar in age, height, weight, TBSA burned, and length of hospitalization. Whole-body LM increased in the EX group ( p  = 0.041) and trended toward an increase in the EX + WBV group ( p  = 0.055). On the other hand, there were decreases in leg BMC for both groups (EX, p  = 0.011; EX + WBV, p  = 0.047), and in leg BMD for only the EX group (EX, p  < 0.001; EX + WBV, p  = 0.26). Truncal BMC decreased in only the EX group (EX, p  = 0.009; EX + WBV, p  = 0.61), while BMD decreased in both groups (EX, p  < 0.001; EX + WBV group, p  < 0.001). Leg strength increased over time in the EX group ( p  < 0.001) and the EX + WBV group ( p  < 0.001; between-group p  = 0.31). Conclusions: Exercise in combination with WBV may help attenuate regional bone loss in children recovering from burns. Studies are needed to determine the optimal magnitude, frequency, and duration of the vibration protocol, with attention to minimizing any potential interference with wound healing and graft closure.